Sex Differences In Duration Of Pre-hospital Delay In Patients With Acute Myocardial Infarction - Maryam Momeni; Arsalan Salari; Atefeh Ghanbari; Maryam Shakiba (Tehran University of Medical Sciences, 2013)
Background and Aim: Pre-hospital delay is an important cause of increasing mortality in acute myocardial Infarction. There are conflicting data regarding the relationship between sex and pre-hospital delay for patients with acute myocardial Infarction. The aim of the present study was to determine the relationship between pre-hospital delay and sex. Materials and Methods: This cross-sectional survey was conducted on 162 consecutive patients with acute myocardial Infarction admitted to Cardiac Care Unit (CCU) in Dr. Heshmat hospital in Rasht between May 2010 and September 2011. A convenient sampling method was used. All patients were interviewed within 7 days after admission by using a data collection form. Results: Mean of pre-hospital delay for women was more than men. Majority of men had chest pain. The women often experienced different and non specific symptoms compared to men. Regression analysis showed no significant relationship between patients' characteristics and pre-hospital delay in women whilst, pre-hospital delay was significantly related to perceiving symptoms to be serious and interpreting symptoms to a cardiac origin in men. Conclusion: Results of the current study suggest that pre-hospital delay for women was longer than men with acute myocardial Infarction as women often experienced no specific symptoms compared to men. Therefore, it recommended that clinicians educate public, particularly women, on acute myocardial infarction to enable them to recognize the signs and symptoms of acute myocardial infarction correctly and realize the benefits of early treatment.